Effects of the “Active Communication Education” Program on Hearing-Related Quality of Life in a Group of Italian Older Adults Cochlear Implant Users - Giallini, Ilaria; Nicastri, Maria; Inguscio, Bianca M. S.; Portanova, Ginevra; Magliulo, Giuseppe; Greco, Antonio; Mancini, Patrizia (Frontiers in Psychology, 2022)
The present study was designed to evaluate the effects of the Active Communication Education (ACE) program on the social/emotional impacts of hearing loss (HL) in a group of older adults with cochlear implant (CI). Design: prospective cohort study design with a “within-subject” control procedure. Study sample: Twenty over-65 adults post-lingually deafened CI users. All subjects were required to be native Italian speakers, to have normal cognitive levels, no significant psychiatric conditions and/or diagnosed incident dementia and at least nine months of CI experienc. Materials and Methods: 20 participants were assessed using the Hearing Handicap Inventory for the Elderly (HHIE), the Geriatric Depression Scale (GDS) and the Speech, Spatial and Qualities of Hearing Scale (SSQ) before, during and afterwards with a one and six month follow up. The evaluation of cognitive and audiological characteristics was carried out prior to commencing the ACE program. Results: The ACE program had a positive impact by reducing the social/emotional impacts of HL. Participants seemed to benefit from a rehabilitative approach aimed at improving multilevel skills - such as, comprehension of audiological and hearing dimensions, acquisition of communicative, pragmatic and problem-solving strategiesand interaction and sharing of experiences with peers. Conclusion: The ACE program, although targeting older adults with moderate HL, also seemed to be of benefit for older adults with severe/profound HL CI users. An improvement in social and emotional adaptation to hearing difficulties can in turn significantly promote optimal use of CI in older adults, thereby possibly reducing the risk of losing motivation and engagement in their use and with rehabilitation protocols.